Sustainable Restoration Guided by Scientific and Archival Investigations: The Bio-Cleaning of Lorenzo Duke of Urbino’s Sarcophagus, a Michelangelo’s Masterpiece in the Medici Chapels - Chiara Alisi; Donata Magrini; Silvia Vettori; Barbara Salvadori; Marina Vincenti; Daniela Manna; Monica Bietti; Anna Rosa Sprocati (Heritage, 2022)
The masterpiece this work deals with is the tomb of Lorenzo de’ Medici, Duke of Urbino, completed by Michelangelo around 1533 in the New Sacristy of Medici chapel in Florence. Sacristy underwent an extensive restoration (2013–2020) and Lorenzo’s sarcophagus was addressed in the last phase (2019–2020). The unique history and the mediocre state of conservation of the marble may be related to body decomposition processes that, according to the documentary research, required a scientific approach to tailor an appropriate intervention. The sarcophagus underwent a bio-cleaning procedure, using bacteria belonging to the ENEA-MIRRI (Microbial Resource Research Infrastructure Italian Node) collection. Spectroscopic analysis (FTIR in ATR and in TR—total reflection—mode and XRF) and microscopic analyses allowed a correct diagnosis of the composition of the coherent deposits, guiding the selection of appropriate bacterial strains. Deposits were composed of gypsum, calcium oxalate, calcium phosphates and proteins. Following a laboratory screening and a preliminary test on-site, the three strains, Serratia ficaria SH7, Pseudomonas stutzeri CONC11 and Rhodococcus sp. ZCONT, immobilised in an appropriate supportant gel, were selected by the quality of cleaning obtained. Two applications of the micro-packs, containing each individual strain, were able to remove the centuries-old deposits within 48 h. The bio-cleaning was selective, gradual and respectful of the marble, in accordance with the restorers’ opinion and reflecting the principles of sustainability.